Understandings around the resilience from the public policy and texts of some nongovernmental organizations with seat in Bogotá who work with families in vulnerability situation - Cuervo Cuesta, Juan Jose; Universidad Santo Tomás, Colombia (Universidad Santo Tomás, Colombia, 2007)
This exercise of investigation examines the concepts of resilience within the published public policies and the literature of non governmental organizations who work with vulnerable families. It follows a qualitative methodology and focuses on a theoretical revision of the literature behind resilience. Also, it takes part of a teacher led investigation project: 'Resilience: identification, potentialization and construction.' This investigation views resilience as a personal characteristic by which individuals recognize their inner potential and make good use of external factors to deal with adversity. Key words: Documental investigation, public policy, family, vulnerability, resilience.